“It's Like Being a Parent at Work”: Antiviolence Frontline Work, Boundaries, and Intimacy During COVID-19 - Schwarz, Corinne (Violence against women, 2024)
COVID-19 profoundly shaped how service providers in the antiviolence sector interact with clients, coworkers, and community stakeholders. In addition to stressors inherent in antiviolence work, service providers negotiated new, challenging social distancing and remote communication strategies. In this paper, we analyze interviews with 23 antiviolence workers in the US Great Plains region, focusing on participants’ descriptions of workplace boundaries and intimacy. We demonstrate how COVID-19 both expanded and contracted public/private boundaries and formal/informal connections in antiviolence workers’ daily experiences. Pandemic conditions revealed the pressing need for frontline workers to exercise discretion over levels of intimate engagement with coworkers and clients.